(untitled) (Revista da Tulha, 2016)
Music and popular Portuguese musical instruments, as we know them today, are the result of a long process In which multiple contributions and influences took place. Musical instruments are, along with the oral tradition, a one of the most fascinating aspects of the traits and marks that the travels of the Portuguese spread throughout the five continents. In five Notes, designed for those who wish to know the Music of the Portuguese people, we try to find meaning in what sometimes it seems disconnected, the result of chance and hazard. But in what we recognize the will of the communities and the persistence in the transmission even when in counter-current of secular and religious powers.